2012
DOI: 10.1097/ijg.0b013e3181fc8129
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effect of BAK-free Travoprost on Ocular Surface and Intraocular Pressure in Glaucoma Patients After Transition From Latanoprost

Abstract: Treatment for 12 months with BAK-free travoprost after BAK-preserved latanoprost resulted in fewer ocular surface complications, as indicated by the reduced prevalence of SPK and decreased hyperemia, and no clinically relevant changes in IOP. BAK-free travoprost may have beneficial effects on the ocular surface while showing IOP-lowering efficacy comparable with BAK-preserved eye drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…Earlier published studies have demonstrated that reductions in the frequency and severity of hyperemia can require 3-12 months to show significant differences between latanoprost with BAK and BAK-free treatments in POAG patients [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier published studies have demonstrated that reductions in the frequency and severity of hyperemia can require 3-12 months to show significant differences between latanoprost with BAK and BAK-free treatments in POAG patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well-known that BAK-free PGAs present fewer toxic effects on the ocular surface [8,14,15]. Nevertheless, these preservative-free formulations must demonstrate their ability to maintain the efficacy described for their counterparts that contain a preservative [12,15]. PRO-067 (BAK-free latanoprost at 0.005%) with integrated preservative-free system (low density polyethylene bottle, closure system of high density polyethylene with a silicone valve system), can be used for up to 48 months without refrigeration (store at 30°C ± 2°C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification of normal, mild, moderate, or severe OSD was determined on a scale from 0 to 100. OSD severity was classified as follows: normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23-32), and severe (33-00). Global Evaluation of Overall Tolerability (GEOT) was assessed at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%